2012
DOI: 10.1055/s-0031-1299656
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Tendon Rupture: A Biomechanical Comparison of Transosseous Equivalent Double-Row Suture Anchor Versus Transosseous Tunnel Repair

Abstract: Quadriceps rupture off the patella is traditionally repaired by a transosseous tunnel technique, although a single-row suture anchor repair has recently been described. This study biomechanically tested a new transosseous equivalent (TE) double-row suture anchor technique compared with the transosseous repair for quadriceps repair. After simulated quadriceps-patella avulsion in 10 matched cadaveric knees, repairs were completed by either a three tunnel transosseous (TT = 5) or a TE suture anchor (TE = 5) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 12 publications
(27 reference statements)
0
65
0
2
Order By: Relevance
“…Biomechanical studies were performed and showed no significant difference between anchor repair and patellar drilling holes technique 27 . Hart investigated biomechanical differences between trans-osseous equivalent double-row suture anchor and trans-osseous tunnel repair: he reported that both were effective in terms of strength, repair stiffness and gap formation with similar results, but the transosseous repairs were stronger 28 . Lighthart et al found no significant differences in terms of displacement after 1000 cycles, adding that suture anchors are more expensive but, as confirmed also by Richards et al 24 , Maniscalco et al 25 and Bushnell et al 26 , allow a smaller skin incision and reduce operative times 29 .…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 99%
“…Biomechanical studies were performed and showed no significant difference between anchor repair and patellar drilling holes technique 27 . Hart investigated biomechanical differences between trans-osseous equivalent double-row suture anchor and trans-osseous tunnel repair: he reported that both were effective in terms of strength, repair stiffness and gap formation with similar results, but the transosseous repairs were stronger 28 . Lighthart et al found no significant differences in terms of displacement after 1000 cycles, adding that suture anchors are more expensive but, as confirmed also by Richards et al 24 , Maniscalco et al 25 and Bushnell et al 26 , allow a smaller skin incision and reduce operative times 29 .…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 99%
“…Although Lighthart et al as well as Hart et al published biomechanical studies comparing two different types of reconstruction, their analysis did not overlap with our own due to different materials that were used [37,39]. The "gold standard", transosseous repair, results in an extended length of suture over clinical course.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…Quadriceps tendon rupture is an uncommon clinical entity that requires early surgical management. [1][2][3][4][5]12,17,19 The standard of care is passage of nonabsorbable sutures through transosseous patellar bone tunnels, but repair with suture anchors has been studied as an alternative that allows for less tissue trauma, decreased operative time, safe early initiation of rehabilitation protocols, and reduced risk of patella fracture or damage. 3,7,[10][11][12][18][19][20]21,23 Despite these potential advantages, biomechanical studies have yielded inconsistent results regarding the superiority of suture anchor repair over repair with transosseous tunnels.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]8,9 The standard of care is repair with a nonabsorbable suture passed through transosseous patellar tunnels, often with several weeks of postoperative immobilization to protect the repair. 3,4,7,[10][11][12] Reported complications of this method include significant extension lag, decreased strength, and ROM compared with the contralateral knee, chronic pain, and iatrogenic patellar fracture. 8,[13][14][15][16][17][18] Repair techniques using suture anchors have been proposed as viable alternatives, but biomechanical studies comparing them with standard transosseous repair have reported mixed results.…”
mentioning
confidence: 99%
See 1 more Smart Citation